Influence of high intensity interval training under hypoxic conditions on acute regenerative capacity during a set of four minutes time trails - de Marees, M.; Abel, B.; Mester, J. (3rd International Congress on Science and Nordic Skiing - ICSNS 2015. 5-8 June 2015, Vuokatti, Finland, 2015)
INTRODUCTION: Among elite level endurance athletes hypoxic training became increasingly popular during the last decades. However the effectively in terms of improving the performance under normoxic conditions is still doubtful, especially by using the intermittent hypoxic training design. Recent studies show an enhancing effect of high intensity interval training under hypoxic (HIITH) conditions on repeated sprint ability (1). So we questioned whether HIIT under hypoxic compared to normoxic conditions may lead to a greater acute regenerative capacity during a set of four minutes of high intensive exercise. The ability to regenerate is one major factor for competing successfully in sports like Paralympic cross country sprint events, where athletes perform three to five time trails separated by 20 min breaks.